Firms' participation in the Swiss COVID-19 loan programme - Lucas Marc Fuhrer; Marc-Antoine Ramelet; Jörn Tenhofen (Swiss Journal of Economics and Statistics, 2021)
This paper analyses the determinants of firm participation in the Swiss COVID-19 loan programme, which aims to bridge firms' liquidity shortfalls that have resulted from the pandemic. State-guaranteed COVID-19 loans are widely used by Swiss firms, with 20% of all firms participating, resulting in a sizeable programme of 2.4% of GDP. We use a comprehensive dataset to study the determinants of firm participation. Our results can be summarised as follows. First, participation was largely driven by the exposure of a firm to lockdown restrictions and to the intensity of the virus in the specific region. Second, we show that firms associated with lower liquidity ratios had a significantly higher probability of participating in the programme. Third, we find no clear evidence that firm indebtedness affected participation in the programme and no evidence that pre-existing potential "zombie firms" participated more strongly in the loan programme. Fourth, we show that the programme reached younger and smaller firms, which could be financially more vulnerable as they are less likely to obtain outside finance during a crisis. Overall, we conclude that given its objective, the programme appears to be successful.
Keywords: D22; H81; 330; COVID-19; Loan programme; Guarantees; Firm behaviour